Changes in bacterial communities of tray-packaged pork during chilled storage analyzed by PCR-TRFLP - JIANG Yun; GAO Feng; XU Xing-lian; YE Ke-ping; ZHOU Guang-hong (浙江大学学报. 农业与生命科学版)
PCR-terminal restriction fragment length polymorphisms (PCR-TRFLP) combined with the method of 16S rRNA gene clone library building and sequencing were used to investigate the changes in the bacterial communities of tray-packaged pork during 4℃ storage. The results showed that 35 terminal restriction fragments (TRF) were observed in the TRFLP profiles, indicating that the composition of bacteria population in chilled pork was complex. The peak of the TRF corresponding to Pseudomonas varied significantly during the whole storage, and the relative peak area continued to increase from 5.7% at day 0 to 83.4% at the end of monitoring, which indicated that Pseudomonas became the predominant bacterial species in the end.